2019
DOI: 10.1177/0019556118814937
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Dynamics of Deliberative Democracy in Rural India: Lessons from the Working of Gram Sabhas in India and Gram Sansads in West Bengal

Abstract: Deliberative democracy has gained considerable momentum in India in recent years in the wake of a new drive for decentralisation and democratisation to promote good governance. The constitutional amendment made in India in 1992 sought to institutionalise this concept in villages through a body called Gram Sabha (village assembly). The amendment mandates the constitution of this institution at the Gram Panchayat level (usually a cluster of villages), the functional details of which have been left to the hands o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Moreover, foregrounding plurality also invites exploring how possible courses of action presented in the literature reviewed in this paper may intersect: to open up the political and contestable nature of the issues at hand, to create space for dissensus thereon, and to explore alternative solution pathways [110]. As a consequence, traditional governance interventions may need to give way to more pluriform, reflexive and adaptive forms of governance [111][112][113][114]. Overall, foregrounding plurality would allow for challenging and transgressing the very ways of thinking and doing that may have played a role in the emergence of the problem(s) at hand in the first place.…”
Section: From Universality To Plurality: Opening Up To a Wider Diversity Of Voicesmentioning
confidence: 99%
“…Moreover, foregrounding plurality also invites exploring how possible courses of action presented in the literature reviewed in this paper may intersect: to open up the political and contestable nature of the issues at hand, to create space for dissensus thereon, and to explore alternative solution pathways [110]. As a consequence, traditional governance interventions may need to give way to more pluriform, reflexive and adaptive forms of governance [111][112][113][114]. Overall, foregrounding plurality would allow for challenging and transgressing the very ways of thinking and doing that may have played a role in the emergence of the problem(s) at hand in the first place.…”
Section: From Universality To Plurality: Opening Up To a Wider Diversity Of Voicesmentioning
confidence: 99%
“…Many a time the villagers are not duly informed about the venue and timings of the meetings. Attendance of women is far from satisfactory (Datta, 2019a). One study has indicated that most of the GPDPs focus on infrastructure like roads canals ignoring human development aspects like education and health.…”
Section: Decentralised Planning: the District Planning Committeesmentioning
confidence: 99%
“…Right to Information has strengthened their hands. But one has reasons to be doubtful about the bright future of Panchayati Raj as a new unit of India’s federation because globalisation and liberalisation are throwing challenges to the liberal concept of local autonomy (Datta, 2019b).…”
Section: Concluding Observationsmentioning
confidence: 99%
“…Third, the public can bring in new perspectives on science and policy discourse by raising concerns or suggesting new ideas that may otherwise be overlooked. This could increase the feasibility and quality of decisions [13,14]. PE in decision-making can be executed in various modes, which are context-specific.…”
Section: Introductionmentioning
confidence: 99%